Inkluzja edukacyjna na etapie szkoły podstawowej w odniesieniu do postaw rodziców dzieci z niepełnosprawnościami = Educational inclusion on the primary school level in reference to the attitudes of parents of children with disabilities - Kościuk, Malwina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article has been dedicated to the research on the attitudes of parents of children with disabilities towards educational inclusion. Due to the choice of the topic, definitions of some key terms have been presented: educational inclusion, attitude, disability. There were some attempts to determine whether the age and education of the caretakers as well as the educational level their children correlate with their attitudes towards inclusion. Three hypotheses have been formulated for this paper. The research group included 31 people, aged from 28 to 55. In order to obtain data, the Survey of Attitudes Toward the Inclusion of Students with Special Needs by M.A. Winzer (adaptedby W. Pilecka and J. Kossewska) has been used. The obtained results have been statistically analyzed with IBM SPSS Statistics v. 29.
Keywords: rodzice; włączenie edukacyjne; postawa; niepełnosprawność; parents; educational inclusion; attitudes; disability